Antibacterial Effects of Star Fruit Extract Against Streptococcus sanguinis - Purba, Member Reni; Gusbakti Rusip; Salsabilah (HM Publisher, 2024)
Streptococus sanguinis is a pioneer bacteria that colonize the oral cavity, plays a role in plaque formation, and contributes to the development of dental caries. Plaque control is needed to inhibit the growth of microorganisms that cause caries by using herbal plants such as starfruit. The aim of the research was to determine whether or not there was an antibacterial effect of starfruit extract (Averrahoa bilimbilin).) against the bacteria Streptococus sanguinis. This research includes laboratory experiments with the sample as a pure culture of Streptococus sanguinis obtained from the Microbiology Laboratory of North Sumatra University Hospital. There were 5 treatment groups (starfruit extract concentration 6.25%, 12.5%, 25%, 50%, 75%), positive control (chlorhexidine 0.2%), and negative control (DMSO). The antibacterial effect was tested using the disc diffusion method. Then, the data was analyzed using statistical tests, one-way ANOVA, and, after this, LSD. The research results were obtained mean, and standard deviation of the diameter of the inhibition zone of star fruit extract, concentrations of 12.5%, 25%, 50%, 75%, and positive control for bacteria Streptococus sanguinis were 7.05 ± 0.192 mm, 9.38 ± 0.171 mm, 13.38 ± 0.171 mm, 14.30 ± 0.216 mm, and 14.38 ± 0.096 mm, while the concentration of star fruit extract was 6.25% and the negative control no inhibition zone was found. Test results from one-way ANOVA revealed that there was a significant antibacterial effect of star fruit extract against the bacteria Streptococus sanguinis (p≤0.05). Test results after this LSD found that the antibacterial effect of the 75% concentration extract was not significant with the positive control, and the 6.25% concentration was not significant with the negative control (p>0.05). From the research results, it can be concluded that the higher the concentration of the extract, the higher the antibacterial effect, with the most effective concentration being 75% and the MIC at a concentration of 12.5%.